Implementation of Corporate Social Responsibility of PT Semen Indonesia Through Women’s Empowerment Program in Ngampel Village, Blora, Central Java - Gan Gan Giantika; Siti Qona’ah (Jurnal Multidisiplin Sahombu, 2026)
Women's empowerment is an important aspect of village development. Women are an integral part of society who have great potential and contribute to social, economic and cultural progress in the village. Women in Ngampel village, Blora, Central Java before 2020, have limited access to education and training, so they are stuck in agricultural work and economic limitations as well as environmental pollution conditions in the Lusi River. PT Semen Indonesia implements a Corporate Social Responsibility Program through women's empowerment to address economic and environmental problems in Ngampel village, Blora. This research uses a qualitative methodology with a case study method. Data collection methods include observation, literature review, and documentation. The implementation of PT Semen Indonesia's Corporate Social Responsibility through the women's empowerment program "Bumi Kartini" carries out three main activities, namely the movement to grow crops in home yards and the management of cow waste into organic fertilizer as well as the establishment of a waste bank in collaboration with BUMDes, PKK and Pegadaian. The implementation of PT Semen Indonesia's Corporate Social Responsibility through the women's empowerment program "Bumi Kartini" has succeeded in overcoming the economic and environmental problems faced by the people of Ngampel Village, Blora, Central Java.